Autophagic flux is required for the synthesis of triacylglycerols and ribosomal protein turnover in Chlamydomonas. (19th October 2017) - Couso, Inmaculada; Pérez-Pérez, María Esther; Martínez-Force, Enrique; Kim, Hee-Sik; He, Yonghua; Umen, James G; Crespo, José L
Abstract : Inhibition of autophagic flux prevented the synthesis of triacylglycerols, formation of lipid bodies, and degradation of ribosomal proteins RPS6 and RPL37 in nitrogen- or phosphate-starved Chlamydomonas cells. Abstract: Autophagy is an intracellular catabolic process that allows cells to recycle unneeded or damaged material to maintain cellular homeostasis. This highly dynamic process is characterized by the formation of double-membrane vesicles called autophagosomes, which engulf and deliver the cargo to the vacuole. Flow of material through the autophagy pathway and its degradation in the vacuole is known as autophagic flux, and reflects the autophagic degradation activity. A number of assays have been developed to determine autophagic flux in yeasts, mammals, and plants, but it has not been examined yet in algae. Here we analyzed autophagic flux in the model green alga Chlamydomonas reinhardtii . By monitoring specific autophagy markers such as ATG8 lipidation and using immunofluorescence and electron microscopy techniques, we show that concanamycin A, a vacuolar ATPase inhibitor, blocks autophagic flux in Chlamydomonas . Our results revealed that vacuolar lytic function is needed for the synthesis of triacylglycerols and the formation of lipid bodies in nitrogen- or phosphate-starved cells. Moreover, we found that concanamycin A treatment prevented the degradation of ribosomal proteins RPS6 and RPL37 under nitrogen or phosphate deprivation. These results indicate that autophagy might play an important role in the regulation of lipid metabolism and the recycling of ribosomal proteins under nutrient limitation in Chlamydomonas .